Loss of miR-16 contributes to tumor progression by activation of tousled-like kinase 1 in oral squamous cell carcinoma. Issue 18 (17th September 2018) - Hu, Shousen; Wang, Honghan; Yan, Dan; Lu, Wuhao; Gao, Pei; Lou, Weihua; Kong, Xiangzhen
ABSTRACT: A different expression signature of miRNA in oral squamous cell carcinoma (OSCC) has been validated. MicroRNA-16 (miR-16) as one of the distinctly dysregulated miRNAs in OSCC, its functional role in progression of OSCC remains not fully clear. Herein, miR-16 expression was significantly lower in OSCC tissues compared to that in adjacent normal tissues ( n  = 131). A lower level of miR-16 was found to be associated with poor prognosis on a cohort of 131 patients with OSCC, and on an extensive public data (457) from TCGA database. Additionally, expression of TLK1 was significantly higher in OSCC tissues compared to that in adjacent normal tissues, which is negatively correlated with miR-16 expression in OSCC. Bioinformatics analyses exhibited that TLK1 is a potential downstream effector of miR-16 by directly targeting the 3′-untranslated regions (3′-UTR) of mRNA. Forced expression of miR-16 in OSCC cell lines inhibits cell proliferation in vitro, and tumor growth in vivo by inhibition of TLK1. Mechanistically, downregulation of TLK1 by miR-16 enhances higher level of DNA damage leading to a significant increase of G2 /M arrest in SCC9 cells. And, overexpression of TLK1 substantially reduces DNA damage and G2 /M arrest by activation of TLK1-dependent cell cycle checkpoint response. To conclude, miR-16 is downregulated in OSCC and serves as tumor suppressor in OSCC progression by targeting TLK1, which has potential to be the novel therapeutic targets and diagnostic biomarkers for OSCC.